ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT PASIEN POLIKLINIK PENYAKIT DALAM UNTUK MEMANFAATKAN KLINIK BERHENTI MEROKOK DI RUMAH SAKIT UMUM DAERAH KOTA YOGYAKARTA - , Wina Widiastuti; , Dra. Yayi Suryo Prabandari, M.Si., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The World Health Organization in 2008 has introduced MPOWER strategy. An effort relevant with strategy 3 of MPOWER is helping someone to quit smoking through the provision of smoking cessation clinic. In 2009 there were 18 smoking cessation clinics spread all over health services and government institutions. At Jogja Hospital there was also smoking cessation clinic but itâs now not in operation due to low utilization. According to Planned Behavior theory, oneâs intention to behave is affected by three main factors, ie. 1) attitude, 2) subjective norm such as social pressure and motivation, 3) perception, besides factors of age and background of disease. Objective: To find out association between age, present disease, attitude, social pressure, motivation, perception and intention of the patient of internal medicine polyclinic to utilize smoking cessation clinic and enabling factors of the implementation of smoking cessation clinic at Jogja Hospital. Method: The study used a cross sectional design. Population were patients at internal medicine polyclinic. Samples that met inclusion criteria consisted of 110 respondents selected through systematic random sampling and also three respondents for qualitative data. Research instruments were closed questionnaire and indepth interview guide. Data analysis used univariate with frequency distribution table, bivariate with Pearson product moment and chi square test, whereas multivariate analysis used double linier regression. Result: There was association between social pressure, motivation, perception and intention to utilize smoking cessation clinic